Issues of improvement of non-governmental organizations services quality and their interaction with the state authorities in Kazakhstan. (Journal of Economic Research & Business Administration, 2016)
The analysis of the causes and preconditions for entry in December 2015 in the legislative acts of Kazakhstan on the activities of non-governmental organizations is very significant changes and additionsconducted. We prove the validity of the legislators’ attention to the problems of improving the interaction of state bodies and improve the efficiency and quality of services to NGOs at the present stage of social modernization of Kazakhstan’s society. The basic innovations of the Law “On amendments and additions to some legislative acts of Kazakhstan on the activities of non-governmental organizations” and the expected results of their implementationdescribed. It is shown thatthe newlawcreates entirely newpreconditions for the NGOdevelopment. Further prospects for improving cooperation between state bodies and improve the efficiency and quality of services to NGOs, the media, and which - to strengthen the role of NGOs as an institution of social control in the area of quality management services to NGOsformulated.
Keywords: non-governmental organization; interaction of state bodies and NGOs; effectiveness and quality of services to NGOs; funding of NGOs; entirely newpreconditions for the NGOdevelopment; public control over the quality of services to NGOs.